From game engagement to craving responses – The role of gratification and compensation experiences during video-gaming in casual and at-risk gamers - S. Antons; M. Liebherr; M. Brand; A. Brandtner (Addictive Behaviors Reports, 2023)
Introduction: Although playing videogames is a common leisure activity some individuals develop problematic gaming behaviors or even symptoms of a gaming disorder. Game engagement may be involved in reinforcement learning that may result in experiences of craving, an important feature of gaming disorder. In the following study we aimed to approach the question which aspects contribute to increased craving for gaming. Methods: Overall, 439 individuals participated in an online survey, answering questionnaires on game engagement, experience of gratification and compensation, craving, and symptoms of gaming disorder. A mediation model testing if the association between game engagement and facets of craving are mediated by the experience of gratification and compensation during gaming. Results: Three facets of craving (reward/relief, physiological, obsessive craving) were statistically explained by game engagement and the experience of gratification and compensation. Models differed between casual gamers and at-risk gamers. The effects on reward/relief and physiological craving were fully mediated in the casual group and partially mediated in the at-risk group by gratification and compensation experiences. Conclusion: Game engagement may contribute to the development of craving by increasing the experience of gratification and compensation and thus might be important in reinforcement learning. Games evoking a high engagement may therefore have a higher addictive potential. Further processes potentially related to game engagement, such as intrusive thoughts and desire thinking, which are related to craving experiences, should be considered in future studies.